The Fritsch-Buttenberg-Wiechell rearrangement: Modern applications for an old reaction - Jahnke, Eike; Tykwinski, Rik (Chemical Communications, 2010)
The Fritsch-Buttenberg-Wiechell rearrangement of carbene/carbenoid intermediates has evolved into a valuable synthetic methodology for the preparation of polyyne structures. Various synthetic routes toward the formation of the corresponding precursors, alkynyl-substituted dibromoolefins, have been developed. Additionally, the scope of this methodology is expanded significantly by the development of functional group-tolerant one-pot procedures. The preparation of various polyynes up to the octa- and decaynes is, thus, possible on a scale that enables thorough physico-chemical characterization. Hence, series of polyynes have been investigated by, e.g., UV-vis, IR- and Raman spectroscopy, as well as X-ray crystallography. These investigations give unique insight into the structural characteristics of longer polyynes and hint to the structure of carbyne. © 2010 The Royal Society of Chemistry.